The Impact of Cognitive Ability Testing on Students with Special Education Needs and Disabilities in Primary Schools in Dubai and Sharjah - SAWALHA, OMAIMA SAMI (2024)
This research aims to investigate the effects of administering cognitive ability tests on students with special educational needs and disabilities (SEND) in primary schools in Dubai and Sharjah. It is hoped that the findings can support the improvement of assessing the needs of students with SEND. Additionally, the study seeks to examine the extent of access to cognitive ability tests by students with various diverse needs. A mixed-research method approach has been followed. The quantitative data collection included conducting a survey among 215 respondents, parents, and teachers, while the qualitative data collection was conducted via interviews among 16 inclusive school leaders, specialists, and teachers within Dubai and Sharjah. A systematic review of the literature was also conducted. The findings entailed that cognitive ability testing has positive impacts on identifying the needs of students with SEND. The results indicate that cognitive ability tests can enhance the academic performance of students with SEND. This research suggests enhancing assessment practices and refining cognitive ability testing procedures and accessibility to ensure they effectively measure the diverse needs and abilities of students with SEND. Additionally, the study recommends a set of possible measures to make the best use of the findings of such tests to enhance and maximize the learning experience for students with SEND.